Pengaruh Penyuluhan Kesehatan terhadap Perilaku Hidup dan Sehat Masyarakat Surabaya - hubbi; Muhammad Ikhlasul Arifin; Mochammad Rafi Ramadhani; Nasyah Rafi Ahmad; Nihlatul Falasifah (Poltekkes Kemenkes Bengkulu, 2026)
Clean and Healthy Living Behavior (PHBS) transcends mere health rules; it embodies public consciousness for the preservation of dignity and quality of life. Nonetheless, the prevailing circumstances indicate that the majority of individuals continue to encounter constraints in the knowledge and practices required to incorporate PHBS into their everyday routines. Health education functions not merely as a conduit for information, but also as an empowerment mechanism that cultivates optimism, enhances awareness, and fortifies a collective feeling of responsibility for a better existence. This study seeks to assess the impact of health education on alterations in community PHBS behavior. The study employed a quantitative methodology with a pre-test and post-test design, involving several respondents from the community affected by the educational initiatives. The data were evaluated to assess the degree to which schooling influenced the enhancement of PHBS knowledge, attitudes, and practices